DEVELOPMENT OF INTERACTIVE LEARNING MEDIA USING PLAYING CARDS ON INDONESIAN HISTORY MATERIAL FOR JUNIOR HIGH SCHOOL STUDENTS - Assidiq, Jimi Priyo; Syaifuddin, Mohammad; Arista Asih, Ria (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
This research aims to develop an interactive learning media based on playing cards through the Wordwall platform that is practical, effective and interesting to improve  Students' recall skills of Indonesian History subject matter. Creative and innovative teachers are important factors in supporting the improvement of students' understanding. The method used is Research and Development (R&D) with the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. The research subjects were male VIII grade students at SMP Muhammadiyah 4 Tanggul. The instruments used include product validation questionnaires by media experts and material experts, student response questionnaires to assess practicality, as well as pre-test and post-test to measure learning outcomes. The results showed that at the analysis stage, students need interactive learning media. The validation results showed that the media met the eligibility criteria, with a score of 82.5% from media experts and 78% from material experts. The practicality test conducted on students resulted in a score of 79%, which is included in the "practical" category. Based on these findings, the playing card-based learning media through the Wordwall platform is declared valid, practical, and effective in improving students' understanding of Indonesian History material